GE_GERICHTE P/1444/2020 vom 2. November 2022 - GE Cour de justice (2022)
PORNOGRAPHIE;IN DUBIO PRO REO;EXPULSION(DROIT PÉNAL);FIXATION DE LA PEINE;SÉJOUR ILLÉGAL | CP.197.al4; CPP.265.al1; CP.47; CP.49.al1; CP.34; CP.42; CP.66a.al2; LEI.115.al1.letb; LEI.115.al1.letc